Hybrid DES-RSA Model for the Security of Data over Cloud Storage - Yadav, Rajan Kumar; Saran, Munish; Devi, Sangeeta; Tripathi, Upendra Nath (International Journal of Computer Sciences and Engineering, 2023)
Cloud computing is a novel business strategy. Over the past several years, the idea of cloud computing has matured, becoming one of the most rapidly expanding business concepts in the IT sector. The capacity of cloud computing to supply consumers with elastic, dependable, and reasonably priced services on demand has contributed to its meteoric rise in popularity in recent years. Since cloud computing provides users with scalable, on-demand services while requiring less investment in infrastructure. Client data and computations must be protected from both internal and external threats in order to allay fears that cloud computing is inherently insecure. This is due to the fact that cloud users get the required information from distant cloud servers that are not under the direct management of the data owners and that the data owners store their sensitive information on remote hosts. The client has the option of implementing security measures such as firewalls, VPNs, and other perimeter-based controls to safeguard their information. Data stored in the cloud raises privacy and security concerns since it is not located on the client`s premises. Therefore, data security is a major focus area in the cloud computing industry. To address these issues with cloud data security, we have developed solutions and strategies. Collectively, the models we`ve offered to ensure data security, privacy, and integrity constitute comprehensive principles for bolstering cloud data security. Cloud security risks and privacy issues, as well as the types of assaults and threats to which clouds are susceptible, are all addressed in the models. We`ve also solved the problem of how to store data on the cloud effectively. Additionally, we propose a general security model for cloud computing that might assist in satisfying its security requirements and safe guarding clouds from different hazardous behaviors.